Binomial Sums?

Algebra Level pending

Evaluate k = 0 n ( n k ) a k ( 1 a ) n k \large \sum_{k=0}^{n} \binom{n}{k}a^{k}(1-a)^{n-k}

Notation: ( n m ) = n ! m ! ( n m ) ! \dbinom nm = \dfrac {n!}{m!(n-m)!} denotes the binomial coefficient .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

James Watson
Jul 26, 2020

k = 0 n ( n k ) a k ( 1 a ) n k ( a + ( 1 a ) ) n \sum_{k=0}^{n} \binom{n}{k}a^{k}(1-a)^{n-k} \equiv \left( a + (1-a)\right)^n

( a + ( 1 a ) ) n = 1 n = 1 \left( a + (1-a)\right)^n = 1^n = \boxed{1}

The brackets ( ) for a k a^k and 1 n 1^n are unnecessary.

Chew-Seong Cheong - 10 months, 2 weeks ago

Log in to reply

ah yes, thanks for letting me know!

James Watson - 10 months, 2 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...